The effect of oil extraction of the oil palm empty fruit bunch on the processability, impact, and flexural properties of PVC-U composites - Abu Bakar, Aznizam (Taylor & Francis, 2006)
The use of oil palm empty fruit bunch fiber (EFB) as reinforcement in the unplasticized poly(vinyl chloride) (PVC-U) is a new attraction in the thermoplastic composite technology. The objectives of this study are to investigate the effects of extracted EFB on processability, impact, and flexural properties of PVC-U composites. A soxhlet extraction was used to extract the extractives from the EFB fibers. The identification of the related functional groups present in the concentrated extract was analyzed using FTIR. To produce composites, PVC resin, EFB fiber, and other additives were first dry-blended using a heavy-duty laboratory mixer before being milled into sheets on a two-roll mill. Test specimens were then hot pressed after which the impact and flexural properties were determined. The processability studies of dry blends were carried out using a Brabender Torque Rheometer model PL2200. The FTIR analysis showed that the oil residue was successfully extracted from EFB fibers. Both the extracted and unextracted fibers decreased the fusion time and melt viscosity of PVC-U. However, the extracted fiber was found to increase the fusion time of PVC as the fiber content increased from 10 to 40 phr. The impact and flexural properties of composites were not significantly affected by the fiber extraction.